Characterization of grape extracts from Vitis vinifera L. varieties grown in Alentejo: phenolic and biochemical assessment - Rouxinol, Maria Inês Silva Caçador Pereira (2023)
The red grape varieties of Vitis vinifera L. have a huge impact on the wine world economy due to the high production of wine in different regions. Grapes are rich in polyphenols that improve wine quality. In addition, moderate consumption of red wine has been shown to be beneficial for health. The composition of each variety may depend on the terroir, being directly affected by factors such as climate change. In this study, four red wine grape varieties commonly produced in the Alentejo were selected and evaluated throughout ripening during two different climate conditions. During this period, the evolution of the berry composition, the phenolic composition of the different varieties, anthocyanin profile and the antioxidant activity of skin extracts were evaluated. In addition, stress enzymatic activity of grape extracts was carried out to estimate grape quality. Additionally, a rapid method based on NIR was developed to provide information on quality parameters in a faster and more cost effectively way than traditional methods. Results shows an impact of different climatic conditions on the grape berries size, and quantity of phenolic compounds, including anthocyanins, indicating that the evaluation of these compounds is important to estimate the best harvest date. The grape skin extracts showed high antioxidant potential, with ability to eliminate free radicals, to protect iron oxidation and to inhibit lipid peroxidation. In addition, PLS models built to create rapid quantification methodologies have shown that these methods have potential for routine use in laboratory; Resumo: Caracterização de extratos de uva de castas Vitis vinifera L. produzidas no Alentejo: avaliação fenólica e bioquímica As castas tintas de Vitis vinifera L. têm um enorme impacto na economia vitivinícola mundial devido à elevada produção de vinho em diferentes regiões. As uvas são ricas em polifenóis que melhoram a qualidade do vinho. Além disso, o consumo moderado de vinho tinto demonstrou ser benéfico para a saúde. A composição de cada variedade depende do terroir, sendo diretamente afetada por fatores como as alterações climáticas. Neste estudo, foram selecionadas e avaliadas quatro castas tintas normalmente produzidas no Alentejo e avaliadas ao longo da maturação em duas condições climáticas diferentes. Durante este período, foi avaliada a evolução da composição dos bagos, a composição fenólica das diferentes variedades, o perfil de antocianinas e a atividade antioxidante dos extratos da película. Além disso, foi determinada a atividade enzimática em stress dos extratos de uva para estimar a qualidade da uva. Além disso, um método rápido baseado em NIR foi desenvolvido para fornecer informações sobre parâmetros de qualidade de forma mais rápida e económica do que os métodos tradicionais. Os resultados mostram o impacto de diferentes condições climáticas no tamanho dos bagos e na quantidade de compostos fenólicos, incluindo antocianinas, indicando que a avaliação desses compostos é importante para estimar a melhor data de colheita. Os extratos de película de uva apresentaram elevada atividade antioxidante, com capacidade de eliminar radicais livres, proteger a oxidação do ferro e inibir a peroxidação lipídica. Além disso, modelos PLS construídos para criar metodologias de quantificação rápida mostraram que estes métodos têm potencial para uso rotineiro em laboratório.